Stochastic expression and epigenetic memory at the yeast HO promoter - Zhang, Qian (National Academy of Sciences, 2013)
Eukaryotic gene regulation usually involves sequence-specific transcription factors and sequence-nonspecific cofactors. A large effort has been made to understand how these factors affect the average gene expression level among a population. However, little is known about how they regulate gene expression in individual cells. In this work, we address this question by mutating multiple factors in the regulatory pathway of the yeast HO promoter (HOpr) and probing the corresponding promoter activity in single cells using time-lapse fluorescence microscopy. We show that the HOpr fires in an “on/off” fashion in WT cells as well as in different genetic backgrounds. Many chromatin-related cofactors that affect the average level of HO expression do not actually affect the firing amplitude of the HOpr; instead, they affect the firing frequency among individual cell cycles. With certain mutations, the bimodal expression exhibits short-term epigenetic memory across the mitotic boundary. This memory is propagated in “cis” and reflects enhanced activator binding after a previous “on” cycle. We present evidence that the memory results from slow turnover of the histone acetylation marks.